Perancangan Sistem Pakar Diagnosis Penyakit pada Bayi dengan Metode Forward Chaining Berbasis Android - Viviliani Viviliani; Radius Tanone (Maranatha University Press, 2019)
In infancy, the age of 0-12 months is a very important period in the process of human growth and development. The process of growth and development at this time affects the child's growth and development in the next period and to reduce mortality in infants. Quick and precise information needs from a baby health expert are needed. The method used in making this expert system is forward chaining, where the system is driven by existing facts. These facts are obtained from the patient's physical condition, or referred to as symptoms. With the existence of an android-based expert system, users everywhere can access to the internet and connect. The process of extracting knowledge by means of interviews. Based on the analysis, this expert system has a percentage of program eligibility for use by laymen is 82.7%. Besides that, based on the results of the questionnaire, the ease of the program also gets a large percentage as well